2003
DOI: 10.1037/0033-2909.129.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis and clinical pain.

Abstract: Hypnosis has been demonstrated to reduce analogue pain, and studies on the mechanisms of laboratory pain reduction have provided useful applications to clinical populations. Studies showing central nervous system activity during hypnotic procedures offer preliminary information concerning possible physiological mechanisms of hypnotic analgesia. Randomized controlled studies with clinical populations indicate that hypnosis has a reliable and significant impact on acute procedural pain and chronic pain condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
194
0
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 339 publications
(227 citation statements)
references
References 156 publications
9
194
0
14
Order By: Relevance
“…Trait theories [41] state that individuals vary in their level of hypnotizability, with individuals high in hypnotic suggestibility responding better to hypnotic suggestions. While there is evidence that level of suggestibility has been significantly related to hypnotic outcomes [15,18], studies have also found that individuals low in hypnotizability can also experience improvements in pain after hypnosis [42][43][44], and some research had found no association between level of hypnotizability and outcome [45,46]. Social-cognitive theories suggest that expectancies, motivation, and environmental cues contribute to an individual's responsiveness to hypnotic suggestions and that improvements are made via cognitive changes that alter the affective components of pain [18,45,47,48].…”
Section: Neurophysiological Mechanisms Involved In Pain Perception Anmentioning
confidence: 99%
See 4 more Smart Citations
“…Trait theories [41] state that individuals vary in their level of hypnotizability, with individuals high in hypnotic suggestibility responding better to hypnotic suggestions. While there is evidence that level of suggestibility has been significantly related to hypnotic outcomes [15,18], studies have also found that individuals low in hypnotizability can also experience improvements in pain after hypnosis [42][43][44], and some research had found no association between level of hypnotizability and outcome [45,46]. Social-cognitive theories suggest that expectancies, motivation, and environmental cues contribute to an individual's responsiveness to hypnotic suggestions and that improvements are made via cognitive changes that alter the affective components of pain [18,45,47,48].…”
Section: Neurophysiological Mechanisms Involved In Pain Perception Anmentioning
confidence: 99%
“…For instance, one study found treatment outcome expectancies to be moderately to strongly associated with improvements in pain intensity over time [45]. Overall, while research suggests that there is evidence to support both theories, there is a lack of consistent evidence to suggest that either theory is entirely sufficient to explain why hypnosis is effective [18]. This is an area that needs continued research.…”
Section: Neurophysiological Mechanisms Involved In Pain Perception Anmentioning
confidence: 99%
See 3 more Smart Citations